Arterial Tortuosity: Novel Implications for an Old Phenotype. Issue 5 (May 2019) - Ciurică, Simina; Lopez-Sublet, Marilucy; Loeys, Bart L.; Radhouani, Ibtissem; Natarajan, Nalin; Vikkula, Miikka; Maas, Angela H.E.M.; Adlam, David; Persu, Alexandre
Abstract : Supplemental Digital Content is available in the text.